Laparoscopic surgical treatment for hydrocele of canal of Nuck: A case report and literature review - Liming Wang; Taku Maejima; Susumu Fukahori; Katayose Shun; Daitaro Yoshikawa; Toru Kono (Surgical Case Reports)
Abstract Background Hydrocele of canal of Nuck (HCN) is a rare disease in adult female. The diagnosis and treatment of HCN is still a challenge for surgeons. Case presentation A 56-year-old female presented with recent onset of occasional pain during exercise and an asymptomatic left groin swelling. Ultrasonography results were suspicious for left inguinal hernia incarceration and computed tomography (CT) scan showed no intestinal obstruction, which was considered as HCN. Laparoscopic hydrocelectomy of the HCN and a routine laparoscopic hernia repair via the transabdominal preperitoneal (TAPP) approach were performed. Postoperative pathology showed no malignant lesions or endometriosis. Conclusions The preoperative diagnosis of HCN is extremely important. Surgeons should choose appropriate surgical methods for different anatomical HCNs based on the preoperative diagnosis.